Preparation and characterization of a low viscosity epoxy resin derived from m-divinylbenzene. (March 2023) - Wu, Xiankun; Xu, Chang-an; Lu, Mangeng; Zheng, Xiaole; Zhan, Yingjie; Chen, Bifang; Wang, Kunxin; Meng, Huifa
To explore thermal and mechanical properties of epoxy material, difunctional aromatic epoxy–divinylbenzene dioxide (DVBDO) had been synthesized by epoxidizing divinylbenzene, using the metal acetylacetone compound grafted Fe3O4 particles as the catalyst. The catalyet had high conversion and epoxy selectivity and could be recyclable. Then the polymerization of DVBDO with different diamine curing agents were reported. The structure and viscosity of DVBDO were firstly characterized. Because it had low molecular weight and viscosity, DVBDO had excellent liquidity and formability. Subsequently to clarify the properties of epoxy thermosets, experiments to determine thermal and mechanical performances were carried out, such as differential scanning calorimetry (DSC), thermal gravimetric (TGA), dynamic mechanical analysis (DMA) and tensile test. It could be observed that the thermoset polymers using DVBDO as epoxy matrix had excellent thermal (Tg was about 201°C) and mechanical properties (tensile strength was 131.99Mpa). Possibly considering that this kind of thermoset polymers had higher rigidity and crosslink density. In conclusion, a new type of one-component liquid epoxy encapsulant material with low viscosity, good filling fluidity, strong heat resistance and excellent storage performance had been developed.